2018
DOI: 10.1007/s10639-018-9730-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital game elements, user experience and learning: A conceptual framework

Abstract: The primary aim of this paper is to identify and theoretically validate the relationships between core game design elements and mechanics, user motivation and engagement and consequently learning. Additionally, it tries to highlight the moderating role of player personality traits on learning outcomes and acceptance and suggest ways to incorporate them in the game design process. To that end, it outlines the role of narrative, aesthetics and core game mechanics in facilitating higher learning outcomes through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 111 publications
(112 reference statements)
8
76
2
3
Order By: Relevance
“…Thus, the optimal amount of difficulty should match user’s abilities to the skills required to accomplish each goal [ 27 ]. This result supports the findings of several studies that have indicated that challenge is a critical factor in the success of serious games [ 20 , 29 , 34 , 43 ] and related to players’ learning [ 46 , 50 ]. Regarding knowledge improvement, serious games should incorporate strategies to provide knowledge that players need to learn and integrate to fulfill the goals of the game [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the optimal amount of difficulty should match user’s abilities to the skills required to accomplish each goal [ 27 ]. This result supports the findings of several studies that have indicated that challenge is a critical factor in the success of serious games [ 20 , 29 , 34 , 43 ] and related to players’ learning [ 46 , 50 ]. Regarding knowledge improvement, serious games should incorporate strategies to provide knowledge that players need to learn and integrate to fulfill the goals of the game [ 54 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, goal clarity correlated with children’s learning. This results add support to the findings of studies [ 43 , 47 ] that stated that goal clarity enhances the engagement levels of players and influences learning effectiveness. However, this result contrasts with the findings of other studies [ 46 , 47 , 50 ] that identified that goal clarity does not influence the players’ learning.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Oh and Ryu (2007) suggested that items which include game elements and are in bundle package might increase sales. Game challenges, in-game flow, and player personality are aligned with the game experience (Alexiou & Schippers, 2018). In view of the benefits of game elements usage and aiming to dwindle the gap regarding the impact of game experience on game elements, the following hypotheses have been designed:…”
Section: Literature Reviewmentioning
confidence: 99%
“…formal adalah kumpulan elemen yang membantu dalam membangun struktur gim. Berikut elemen formal yang dapat digunakan dalam membentuk struktur gim[14],[15]: 1. Pemain: pengguna yang memainkan gim baik itu secara individu maupun kelompok.…”
unclassified